PRAKTIK DIAKONIA BERDASARKAN YAKOBUS 2 14–17 DALAM PERSPEKTIF TEOLOGI DAN SOSIOLOGI KRISTEN - Lani Lidia Urio; Semiloka Dimara; Darmawaty Banawa; Agustina Meri; Ina Itlay (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2026)
This study aims to analyze the practice of diakonia based on James 2:14–17 from the perspectives of Christian theology and sociology. It employs a qualitative method using a library research approach, examining the Bible, theological and Christian sociology texts, and relevant scholarly articles. The findings indicate that James 2:14–17 affirms that true faith must be manifested through acts of love as tangible evidence of a believer's life. From a Christian theological perspective, diakonia is part of the *missio Dei*, reflecting God's love through service to others. Meanwhile, the Christian sociology perspective views diakonia as an instrument of social transformation that fosters solidarity, empowers communities, alleviates injustice, and promotes the common good. The implementation of diakonia in the contemporary church requires a holistic approach extending beyond mere charitable aid to include community empowerment and collaboration with various stakeholders. Thus, the practice of diakonia based on James 2:14–17 serves as a concrete expression of living faith and strengthens the church's role as an agent of social change and a witness to the love of Christ within society.